1994
DOI: 10.1007/bf00128605
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ?-glucosidase catalysed synthesis of trisaccharides from cellobiose and gentiobiose

Abstract: Purified 13-Glucosidase from Fusarium oxysporum catalysed the hydrolysis and transglycosylation reactions in the presence of cellobiose and gentiobiose. The product of the latter reaction was mainly a triose. The time of incubation, pH and substrate concentration for transglycosylation reaction were optimised. Under optimal conditions, the concentration of glucose and triose reached approximately 15 -20 % of the initial substrate concentration. These results suggested that 13-glucosidase from F.oxysporum is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…A Maximum GOSs concentration of 112 mg/ml was obtained after 9 h from an initial cellobiose concentration of 350 mg/ ml. Similar findings have previously been described for b-glucosidases from Aspergillus niger (Yan and Liau 1998) and Fusarium oxysporum (Christakopoulos et al 1994). The study of the other reaction-conditions showed, when considering all measured parameters, that the optimum pH was 5 (Fig.…”
Section: Optimal Conditions For Cellobiosetransglycosylation Reactionsupporting
confidence: 83%
“…A Maximum GOSs concentration of 112 mg/ml was obtained after 9 h from an initial cellobiose concentration of 350 mg/ ml. Similar findings have previously been described for b-glucosidases from Aspergillus niger (Yan and Liau 1998) and Fusarium oxysporum (Christakopoulos et al 1994). The study of the other reaction-conditions showed, when considering all measured parameters, that the optimum pH was 5 (Fig.…”
Section: Optimal Conditions For Cellobiosetransglycosylation Reactionsupporting
confidence: 83%
“…Transglycosylation is a kinetically controlled reaction, while the reverse hydrolysis is under thermodynamic control. The synthetic activity of glycosidases has been used for production of oligosaccharides [4][5][6][7][8][9][10][11][12], alkyl-glycosides [12][13][14][15][16][17], vitamin derivatives [18]. Oligosaccharides are used as therapeutic agents, diagnostic tools, and additives in the food and cosmetic industries [8,12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used enzymes for oligosaccharide and alkyl-glycoside synthesis are -glucosidases (EC 3.2.1.21), which act on terminal non-reducing -D-glucosyl residues in cellooligosaccharides and other -D-glucosides with release of -D-glucose [20]. Different -glucosidases from fungi, bacteria and plants have been used in transglycosylation and condensation reactions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][20][21][22][23][24], which are usually carried at high substrate concentration in order to attain higher yields of products. Trisaccharides and higher oligomers are formed as major transglycosylation products of -gluco-*Address correspondence to these authors at the Department of Chemistry, M.V.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Στην υδρόλυση του ß-γλυκανίου συμμετέχουν εκτός από βγλυκοσιδάση, η ένδο-(1-3)-β-0-γλυκανάση και η ß-γλυκανενδοϋδρολάση του κριθαριού. (115,116), ενώ 6-γλυκοσιδάση από Fusarium oxysporum οδήγησε στη σύνδεση τριοζών, σε αντιδράσεις τρανσγλυκοσυλίωσης με υπόστρωμα κελλοβιόζη (117).…”
Section: τρανσγλυκοσυλίωσηunclassified